Analysis of the cost of pharmacotherapy of ischemic stroke in hospital in 2009-2011 - N. V. Mikheeva; O. V. Reshetko; S. I. Kurnosov (Регуляторные исследования и экспертиза лекарственных средств)
Pharmacoeconomic analysis includes the assessment of direct cost structure in pharmacotherapy of cerebral infarction for the period of 2009-2011 in healthcare institutions in Saratov (762 patients) based on ABC analysis and frequency analysis. The results of the mentioned analysis showed the presence of drugs without proven efficacy and a very high associated cost component (75.67%) of purchasing budget in drug group «A». It was revealed, that the drugs of scientifically substantiated efficacy and safety are not used sufficiently in treatment of cerebral infarction. On the other hand the drugs without proven efficacy are widely used, which leads to an increase in financial losses of the state and population. The results of clinical and economic analysis showed the need for changing the cost structure for drug therapy of the mentioned disease in hospitals.